2022
DOI: 10.1038/s41598-022-09945-9
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoprogression prediction in high grade primary CNS tumors by use of radiomics

Abstract: Our aim is to define the capabilities of radiomics and machine learning in predicting pseudoprogression development from pre-treatment MR images in a patient cohort diagnosed with high grade gliomas. In this retrospective analysis, we analysed 131 patients with high grade gliomas. Segmentation of the contrast enhancing parts of the tumor before administration of radio-chemotherapy was semi-automatically performed using the 3D Slicer open-source software platform (version 4.10) on T1 post contrast MR images. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Shi et al also utilized 3D Slicer for preoperative assessments [43,45,47,50]. Additionally, Ari et al [10] and Brown et al [11] leveraged 3D Slicer for extracting and analyzing omics features. Despite the apparent distance from frontline teaching, it is imperative to recognize that a crucial facet of higher education is its application-oriented and employment-focused approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al also utilized 3D Slicer for preoperative assessments [43,45,47,50]. Additionally, Ari et al [10] and Brown et al [11] leveraged 3D Slicer for extracting and analyzing omics features. Despite the apparent distance from frontline teaching, it is imperative to recognize that a crucial facet of higher education is its application-oriented and employment-focused approach.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it supports extensions, with over a hundred open-source extensions available on the platform. These extensions range from radiomics analysis [10,11] to artificial intelligence (AI)-based automatic organ segmentation for medical image analysis [12,13] and from surgical navigation [14,15] to target delineation [16,17] and dose calculation for radiation therapy clinical tools [18,19]. Its extensive functionality surpasses that of professional workstations utilized in clinical environments [20][21][22][23][24].…”
Section: Application Of 3d Slicer Platform In Medical Image Analysismentioning
confidence: 99%
“…131 patients with HGG. [42] Use of the tissue permeability and microcirculation parameters Ktrans, Kep, IAUC to differentiate PT from TM.…”
Section: Major Finding Experimental Systemmentioning
confidence: 99%
“…In a cohort of patients diagnosed with HGG, radiomics and machine learning methodologies were reported as able to help predict the development of pseudoprogression from pre-treatment MR images, thus potentially allowing to reduce the use of biopsy and invasive histopathology [42] (Table 1).…”
Section: Pseudoprogression and Other Post-treatment Effectsmentioning
confidence: 99%
“…Quantitative factors extracted from conventional MRI and CT images (so-called radiomic features) can be used in conjunction with machine learning algorithms to answer important diagnostic questions in the diagnosis of brain tumors in a fully automated, objective, highly precise, and, above all, non-invasive way. For example, Ari et al showed that radiomic-based machine learning can be used to non-invasively predict pseudoprogression in high-grade gliomas [2]. Krähling et al developed an MRI-based radiomics model to predict mitotic cycles in intracranial meningiomas before surgery [3].…”
Section: Introductionmentioning
confidence: 99%